The creation of defects in Cu-doped TiO2 memristive devices - Gu, Bin; Zhang, Bo; Wágner, Tomáš (Springer, 2024)
Memristors are utilized in nonvolatile memory and artificial synaptic devices. However, the industrial application of memristors has been restricted by the occurrence of fatigue, the mechanism of which is still under debate. In this paper, we systematically investigated the mechanism of defect generation created by Joule heating in Cu-doped TiO2 memristive device. The results also demonstrated that the Joule heat for artificial synaptic emulation was less severe than that for digital data storage.
Vznik defektů v memristivních zařízeních z TiO2 dopovaného Cu
Keywords: Physical vapor deposition; Semiconductors; Thin films; Fyzikální napařování; polovodiče; tenké vrstvy